Pd/S cooperativity: from stoichiometric activation of Si−H bonds to catalytic hydrosilylation - Arnaud Clerc; Marceline Humbert; Sonia Mallet‐Ladeira; Dr. Karinne Miqueu; Dr. Julien Monot; Prof. Blanca Martín‐Vaca; Dr. Didier Bourissou (ChemistryEurope)
Abstract With the aim to explore metal‐ligand cooperation across Pd−S linkages, we designed a quinoline‐based PNS tridentate ligand and prepared Pd(II) complexes thereof. Optimal solubility and stability of the dicationic complex [(PNS)Pd(II)]22+ IV2 were achieved with B(C6F5)4– as counter‐anion. It adopts a thiolate‐bridged dimeric structure with a (PdS)2 core, but readily activates hydrosilanes across the Pd−S linkage. The resulting mononuclear Pd(II) hydride [(PNSSiR3)Pd(II)H]+ VI was characterized by multi‐nuclear NMR spectroscopy and the Si−H bond coordination/activation was studied computationally. Complex IV2 was found to efficiently catalyze the hydrosilylation of alkynes, internal as well as terminal, with good stereo and regioselectivity.